2011
DOI: 10.1002/jwmg.54
|View full text |Cite
|
Sign up to set email alerts
|

Bias associated with baited camera sites for assessing population characteristics of deer

Abstract: Camera surveys often involve placing bait in front of the camera to capture animals more frequently, which could introduce biases in parameter estimates. From September 2008 to March 2009, we monitored cameras placed at random, along game trails, and at feed stations to determine if camera placement influenced measures of population demographics in a herd of white‐tailed deer (Odocoileus virginianus). There was no time period in which cameras placed at feed stations provided sex ratio and recruitment estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 26 publications
0
50
0
1
Order By: Relevance
“…We would caution managers from translating spotlight counts into population estimates for stocking rates or other purposes but if they do we would suggest doubling their estimated abundance for very coarse and conservative estimates . We believe a better approach would be to use spotlight data in conjunction with other monitoring methods such as vegetation monitoring, camera surveys, or a variety of other methods (Kraaij & Milton 2006;Ditchkoff 2007;McCoy et al 2011) focused on conditions of the grassland savanna. Additionally, although perhaps cost prohibitive, use of thermal imagers seems to provide a less biased estimate of detection probabilities for ungulates, thus managers could potentially consider thermal imaging for surveying ungulates in African savanna.…”
Section: Discussionmentioning
confidence: 99%
“…We would caution managers from translating spotlight counts into population estimates for stocking rates or other purposes but if they do we would suggest doubling their estimated abundance for very coarse and conservative estimates . We believe a better approach would be to use spotlight data in conjunction with other monitoring methods such as vegetation monitoring, camera surveys, or a variety of other methods (Kraaij & Milton 2006;Ditchkoff 2007;McCoy et al 2011) focused on conditions of the grassland savanna. Additionally, although perhaps cost prohibitive, use of thermal imagers seems to provide a less biased estimate of detection probabilities for ungulates, thus managers could potentially consider thermal imaging for surveying ungulates in African savanna.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that white-tailed deer males can travel twice as far as females in a day (Webb et al, 2010) no bias was observed in detectability by sex or recapture rates for males and females (Roberts et al, 2006;Watts et al, 2008). McCoy et al (2011), highlighting that the main reason for sexual bias corresponds to different responses to bait attraction. Studies that do not use bait have determined sex ratios using camera traps without further discussion (Shields et al, 2012;Ikeda et al, 2013).…”
Section: Camera Trapmentioning
confidence: 91%
“…We did not use bait in the study, as it is subject to controversy (Mccoy et al 2011). Some argue that using bait may overestimate the number or sex of deer, by attracting individuals from other territories (Jacobson et al 1997, Roberts et al 2006.…”
Section: Study Areamentioning
confidence: 98%
“…The most commonly used monitoring techniques rely on indirect methods, such as track and pellet-group counts (Mooty and Karns 1984, Mandujano 2005, Ortíz et al 2005, Reyna-Hurtado and Tanner 2007, Sánchez-Rojas et al 2009). However, these methods are sensitive to habitat, terrain conditions, and the need for trained personnel; further, they do not provide information regarding age structure or sex ratio (Novak et al 1991, Smallwood and Fitzhugh 1995, Mccoy et al 2011). On the other hand, aerial counts, spotlight surveys, thermal imaging, as well as direct counts on foot or in vehicles, are costly, as well as being restricted to open zones and specific seasons (Jacobson et al 1997, Dellafiore et al 2003, Roberts et al 2006, Collier et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation